Lipid metabolic remodeling delays senescence of T cells to potentiate their immunity against solid tumors - Lu Wang; Li Ding; Gang Chen; Zhou Xu; Yanqing Zhang; Bin Deng; Xiya Wang; Yemin Xu; Mengyue Wu; Yinhe Xia; Zhennan Cao; Ruilong Song (Journal for ImmunoTherapy of Cancer)
Background Tumor cells can drive the senescence of effector T cells by unbalancing their lipid metabolism, thereby limiting adoptive T cell therapy and contributing to tumor immune evasion. Our objective is to provide a feasible strategy for enhancing T cell treatment efficacy against solid tumors.Methods In this study, liposomal arachidonyl trifluoromethyl ketone (ATK) was anchored onto the adoptive T cell surface via bioorthogonal reactions, aiming to specifically inhibit the group IVA cytosolic phospholipase A2α (cPLA2α), a key enzyme facilitating phospholipid metabolism and senescent state of T cells.Results The surface engineering exerted rare side effects on the activation and migration of T cells, but local and sustained extravasation of ATK downregulated cPLA2α expression, reprogrammed lipid metabolism, and inhibited lipid droplet accumulation. This endows T cells with delayed senescence and declined apoptosis to maintain their tumor-killing potency. Systemic administration of surface-engineered T cells resulted in superior infiltration in solid tumors and improved antitumor efficacy by enhancing the secretion of cytotoxic molecules, thereby prolonging the survival of mice bearing colorectal carcinoma and melanoma xenografts.Conclusions Lipid-metabolically remodeled T cells with delayed senescence increase efficacy in tumor microenvironment, highlighting a novel strategy for solid tumor immunotherapy.